Zymographic techniques for the analysis of matrix metalloproteinases and their inhibitors. (January 2005) - Snoek-van Beurden, Patricia A.M.; Von den Hoff, Johannes W.
The balance between matrix metalloproteinases (MMPs) and their inhibitors, the tissue inhibitors of metalloproteinases (TIMPs), is largely responsible for the remodeling of tissues. Deregulation of this balance is a characteristic of extensive tissue degradation in certain degenerative diseases. To analyze the role of MMPs and TIMPs in tissue remodeling under normal and pathological conditions, it is important to have reliable detection methods. This review will focus on zymographical techniques for the analysis of MMPs and TIMPs. MMPs can be analyzed with several zymographical techniques, but substrate zymography is the most commonly used. This technique identifies MMPs by the degradation of their preferential substrate and by their molecular weight. Several substrates that can be used for zymography are described. Reverse zymography, which detects TIMPs by their ability to inhibit MMPs, is also discussed. Finally, in situ zymography is described, which is used to localize MMPs in tissue sections. Common problems encountered during sample preparation, zymography itself, and the data analysis are discussed. Hints are given to improve the sensitivity and accuracy of zymographical methods. In conclusion, zymography is a valuable tool for research purposes and for the development of new diagnostic techniques and therapies for pathological conditions such as rheumatoid and osteoarthritis, and tumor progression.